Alteration of neurofilament heavy chain and its phosphoforms reveals early subcellular damage beyond the optic nerve head in glaucoma - Zhou, Lan; Lin, Dongyue; Xu, Guihua; Wang, Xiaoyi; Chen, Zilin; Wang, Dingding; Fan, Huiya (Frontiers in Neurology, 2023)
Background Retinal ganglion cells (RGCs) axon loss at the site of optic nerve head (ONH) is long believed as the common pathology in glaucoma since different types of glaucoma possessing different characteristic of intraocular pressure, and this damage was only detected at the later stage. Methods To address these disputes and detect early initiating events underlying RGCs, we firstly detected somatic or axonal change and compared their difference in acute and chronic phase of primary angle-closed glaucoma (PACG) patient using optical coherence tomography (OCT), then an axonal-enriched cytoskeletal protein neurofilament heavy chain and its phosphoforms (NF-H, pNF-H) were utilized to reveal spatio-temporal undetectable damage insulted by acute and chronic ocular hypertension (AOH, COH) in two well characterized glaucoma mice models. Results In clinic, we detected nonhomogeneous changes such as ONH and soma of RGCs presenting edema in acute phase but atrophy in chronic one by OCT. In AOH animal models, an increase expression of NF-H especially its phosphorylation modification was observed as early as 4 h before RGCs loss, which presented as somatic accumulation in the peripheral retina and at the sites of ONH. In contrast, in microbeads induced COH model, NF-H and pNF-H reduced significantly, these changes firstly occurred as NF-H or pNF-H disconnection at ONH and optic nerve after 2 weeks when the intraocular pressure reaching the peak; Meanwhile, we detected aqueous humor pNF-H elevation after AOH and slight reduction in the COH. Conclusion Together, our data supports that early alteration of NF-H and its phosphoforms would reveal undetectable subcellular damage consisting of peripheral somatic neurofilament compaction, impaired axonal transport and distal axonal disorganization of cytoskeleton beyond the ONH, and identifies two distinct axonal degeneration which were Wallerian combination with retrograde degeneration in acute PACG and retrograde degeneration in the chronic one.